Poultry production in Burkina Faso: Potential for poverty reduction and women’s empowerment - Hoffmann, Vivian; Awonon, Josue; Gelli, Aulo (International Food Policy Research Institute, 2020)
Poultry rearing is widespread in rural Burkina Faso, and contributes to both the food security and cash income of smallholders farmers. The landlocked status of the country, coupled with increasing demand for poultry in urban areas implies an opportunity for significant, pro-poor growth through this sector. We use data from a survey of 1800 poultry producers to characterize smallholder poultry producers and their practices. We find that 88% of households in program areas raised poultry. While access to vaccination services and veterinary medicines at the village level is high, uptake of these services is limited, especially among smaller producers. Fewer women than men own poultry, but most women report that they control the proceeds from sales of their own birds, indicating the potential for development of the poultry sector to generate relatively equitable gains in terms of gender. Access to credit appears to increase women’s poultry ownership, but remains limited, as does women’s access to poultry output markets.